Epidemiological and clinical characteristics of 2019 novel coronavirus disease (COVID-19) in Jilin, China: A descriptive study. Issue 47 (20th November 2020) - Liu, Han; Gao, Jinying; Wang, Yangyang; Jie, Jing; Luo, Jingjing; Xu, You; Sun, Hongying; Song, Lei; Li, Dan; Peng, Liping; Hua, Shucheng
Abstract : Abstract: Coronavirus diseases 2019 (COVID-19) has become a global pandemic. To add to the scarce information on this disease, here, we investigated the epidemiological and clinical characteristics of 93 hospitalized patients with COVID-19 in Jilin, China from January 22 to March 15, 2020. We retrospectively investigated the demographic information, recent exposure history, clinical symptoms or signs, comorbidity, chest computed tomographic (CT) scan or X-ray results, laboratory test results, diagnostic classification, treatment, length of hospitalization, complications, and outcomes. Of the 93 patients, 54 were male and 39 female. More than half of these patients had a history of exposure to infected patients. The mean incubation period was 10.4 days in 87 patients, where the data was available. The 5 most common symptoms of illness onset were fever, cough, expectoration, fatigue, and dyspnea. One patient was asymptomatic. The imaging results were abnormal in majority of the patients. Almost one-third of the patients had lymphopenia. All patients received antiviral therapy, 84 patients were treated with antibiotics and 54 received different doses of the hormone for methylprednisolone. In addition, 72 patients used traditional Chinese medicine. Oxygen therapy, high nasal flow oxygen, non-invasive ventilator, invasive ventilator and extracorporeal membrane oxygenation (ECMO) were used symptomatically in different patients. Except 1 patient who died during treatment, all others were discharged. The average incubation time is prolonged in the present analysis, as compared to that in other reports. A few patients symptoms improved but CT exacerbated. Therefore, we suggest that close follow-up observation is still required after discharge.